The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1659/mrd-journal-d-19-00063.1
|View full text |Cite
|
Sign up to set email alerts
|

Elevation and Child Linear Growth in Nepal

Abstract: The relationship between elevation of residence and a child's linear growth was studied using data for 8824 children below the age of 5 years born between 2001 and 2016 at elevations ranging from 50 to 3200 m above sea level in Nepal. Multiple regression was used to measure the role of a variety of household and community factors in explaining the observed elevation effect. A negative association was found between elevation and linear growth that varied substantially across the sample but retained a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Whether altitude independently contributes to child growth or simply serves as a proxy for differences in underlying patterns of economic development has obvious relevance for targeting policy and project interventions. For example, using data from Nepal, a country with a substantial number of children living at high altitudes, Shively et al (2020) find that household wealth and maternal BMI mitigate the altitude-HAZ relationship. Our confidence that altitude signals underlying drivers in a child's Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether altitude independently contributes to child growth or simply serves as a proxy for differences in underlying patterns of economic development has obvious relevance for targeting policy and project interventions. For example, using data from Nepal, a country with a substantial number of children living at high altitudes, Shively et al (2020) find that household wealth and maternal BMI mitigate the altitude-HAZ relationship. Our confidence that altitude signals underlying drivers in a child's Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Work from Nepal supports this conjecture. A number of studies find that height for age z scores (HAZ) and stunting rates have improved for children below age 5 since 2000, but gains have been largest for children from wealthier and more educated households (Budhathoki et al, 2020;Dorsey et al, 2018;Hanley-Cook et al, 2020;Nepali et al, 2019;Shively, et al, 2020). Characteristics of children and households explain most of the variance in HAZ and weight for height z scores (WHZ) in Nepal, with relatively smaller but statistically significant contributions from community-level factors (Smith & Shively, 2019).…”
Section: Background and Motivationmentioning
confidence: 99%
“…The prevalence of wasting in children under 5 years of age is estimated at 6.1% in the Mountains, 6.4% in the Hills, but 12.2% in the Terai [ 3 ]. A study by Shively et al, showed that “for each 1000 m gain in elevation, height-for-age Z-scores (HAZ) declined by between 0.1 and 0.2 points for an average child and by between 0.35 and 0.42 points for a child with the characteristics of those living at the highest elevations” [ 4 ]. The authors cited several factors beyond economic isolation as potentially contributing to the high stunting rates observed in the mountains, including differences in agricultural production and micronutrient deficiencies (zinc and iron).…”
Section: Introductionmentioning
confidence: 99%